1999
DOI: 10.1002/(sici)1099-0690(199901)1999:1<49::aid-ejoc49>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Oligonucleotides Containing the (4R) and (4S) Diastereoisomers of 4,8-Dihydro-4-hydroxy-8-oxo-2′-deoxyguanosine

Abstract: The insertion of the (4R) and (4S) diastereoisomers of 4,8‐dihydro‐4‐hydroxy‐8‐oxo‐2′‐deoxyguanosine, the two main singlet oxygen oxidation products of 2′‐deoxyguanosine, (4R)‐4‐OH‐8‐oxodGuo (3a) and (4S)‐4‐OH‐8‐oxodGuo (3b), into oligonucleotides has been achieved by means of phosphoramidite chemistry using the solid‐phase synthesis approach. The synthesis of the phosphoramidite synthons 8a and 8b required 6 steps from 2′‐deoxyguanosine and involved the simultaneous protection of the additional tertiary hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Nuclease P 1 was found to be unable to cleave the phosphodiester bonds between normal and altered 2'-deoxyribonucleosides. [18,19] Enzymatic digestion of oligonucleotides containing (5'S,5S,6S)-cyclo-5-OH-dHdU (1) by bovine intestinal mucosa phosphodiesterase (3'-exo) and calf spleen phosphodiesterase (5'-exo): Additional enzymatic digestion experiments were performed on the modified 3-mer 11 by using the two exonucleases bovine intestinal mucosa phosphodiesterase (3'- exo) and calf spleen phosphodiesterase (5'-exo). It was shown that both enzymes failed to cleave the phosphodiester bond on either side of the (5'S,5S,6S)-cyclo-5-OHdHdU (1) residue, as already observed for (5'S,6S)-cyclodHdU and (5'S,6S)-cyclodHT.…”
Section: Resultsmentioning
confidence: 99%
“…Nuclease P 1 was found to be unable to cleave the phosphodiester bonds between normal and altered 2'-deoxyribonucleosides. [18,19] Enzymatic digestion of oligonucleotides containing (5'S,5S,6S)-cyclo-5-OH-dHdU (1) by bovine intestinal mucosa phosphodiesterase (3'-exo) and calf spleen phosphodiesterase (5'-exo): Additional enzymatic digestion experiments were performed on the modified 3-mer 11 by using the two exonucleases bovine intestinal mucosa phosphodiesterase (3'- exo) and calf spleen phosphodiesterase (5'-exo). It was shown that both enzymes failed to cleave the phosphodiester bond on either side of the (5'S,5S,6S)-cyclo-5-OHdHdU (1) residue, as already observed for (5'S,6S)-cyclodHdU and (5'S,6S)-cyclodHT.…”
Section: Resultsmentioning
confidence: 99%
“…However, the hydrolysis of the phosphodiester bonds between 2-4 and normal 2′-deoxyribonucleosides is much slower than that of the corresponding nonmodified ODNs, requiring 26 h of incubation with nuclease P1. Such results suggest a partial inhibition of the endonuclease activity by the lesion in agreement with previously reported data involving short ODNs containing other free radical-and singlet oxygen-induced base modifications (31)(32)(33). To obtain more information about the effect of specific tandem DNA lesions 2-4 on the behavior of nucleases, we have also studied the stability of the modified ODNs toward exonucleases.…”
Section: Resultsmentioning
confidence: 99%
“…Cadet, et al, reported that enzymatic hydrolysis of phosphodiester bonds between 4,8-dihydro-4-hydroxy-8-oxo-dG (later to be corrected as spiroiminodihydantoin (13) and normal 2'-deoxyribonucleosides in oligonucleotides was inhibited with both endonucleases and exonucleases (33). In order to evaluate the effects of various enzymes on the formation of 8-oxodG and spiroiminodihydantoin, untreated calf thymus DNA was digested with 1.)…”
Section: Yields Of 8-oxodg and Spiroiminodihydantoin From Different Dmentioning
confidence: 99%